Saturday

February 28, 2015

February 28, 2015

Posted by **Chris Adison** on Thursday, April 24, 2008 at 10:43am.

MgH = (1/2)*k*(H-2-10)^2 + Mg*2

I was told to expand the square on the right, gather terms, put it in the standard quadratic form, and use the quadratic formula, but I don't know how.

Should it be Mgh=(H-12)^2+25+1685?????

**Answer this Question**

**Related Questions**

physics repost - I am still trying to solve for H in this equation but I am ...

math - A=1/2h (b1 + b2) Solve for b1 A=1/2h (b1 + b2) Solve for b1 I assume this...

math - 2.)If f(x)=3x,g(x)=x-3,and h(x)= the square root of x, find (fogox)(X). ...

math - 2.)If f(x)=3x,g(x)=x-3,and h(x)= the square root of x, find (fogox)(X). ...

Physics-repost, sorry, I still don't understand :( - A forearm with a mass of 1....

Pre-calc - Find the effective rate of interest for 5.25% compounded quarterly. I...

math - Let F1=(-6,0) ,F2=(6,0) A=(10,0)64 + and B=(-10,0) write an equation of ...

Physics repost - A wave traveling in the +x direction has an amplitude of 0.45 m...

maths - how do i solve this equation? 2/(x+1)=1/(x-1) - (1/(2x-1)) thx Get a ...

Substitution Method-Plz help - Use the Substitution method to solve the system ...